MENINGKATKAN HASIL BELAJAR SISWA DENGAN MODEL COOPERATIVE LEARNING TIPE JIGSAW PADA SISWA KELAS V SD NEGERI 16 KOTA PAREPARE - Nur Rahmatan Mursalin (IAIN Palopo, 2018)
The initial idea of this study was the low learning outcomes of students in science lessons, especially green plant material. This is because teachers are less creative in using teaching methods and models that can help students in learning. The main problem in this study is how to improve student learning outcomes in green plants through jigsaw cooperative learning in class V SD Negeri 16 Kota Parepare. This study aims to determine the improvement of student learning outcomes by using a jigsaw type cooperative learning model for grade V students of SD Negeri 16 Kota Parepare. The procedure for activities in research includes planning, action, observation and reflection. Subjects in this study were teachers and students of class V SD Negeri 16 Kota Parepare TA. 2010/2011 with a total of 22 students with details of 14 men and 8 women. Data collection techniques used are observation, test, and documentation techniques. The results showed that student learning outcomes in green plants with the use of jigsaw cooperative learning method in cycle I were categorized as poor (K) then increased in cycle II with categories of Enough (C), and in cycle III categorized as Good (B). Thus, the use of jigsaw cooperative learning method can improve the learning outcomes of grade V students of SD Negeri 16 Kota Parepare.